A heuristic algorithm to schedule twin yard crane to minimize job tardiness in container terminals - Wee, Benathon Yan Zhi (2015)
This project aims to reduce the job tardiness in container terminals. By implementing earliest deadline first algorithm in the Rubber Tyred Gantry (RTG) system, we hope to improve the current algorithm with additional method call look ahead. The main thing that look ahead does is to consider other unassigned job as well. From this project, it shows how this algorithm and the additional method are implemented and included test cases that prove the additional function is working correctly. It also shows that by including the additional function, it improves job tardiness for most of the cases as factors such as the safety distance between the two yard cranes also play a significant role.